Out-of-Field Teaching in Elementary Schools: Preparedness of Pre-Service PPG English Graduates in Indonesia - Khofifah Indah Sari; Soni Mirizon; Machdalena Vianty (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2026)
The Pre-service Teacher Professional Education programme (PPG Prajabatan) in Indonesia faces ongoing challenges related to assignment linearity, resulting in a gap between specialization-based training and classroom realities. This issue is particularly evident among English education graduates assigned to elementary schools and required to teach multiple core subjects beyond their training. This qualitative single-case study investigated how the pre-service PPG programme prepared English education graduates for non-linear teaching roles, focusing on the experiences of English specialists transitioning to generalist roles in elementary schools. Data were collected through semi-structured interviews with graduates in Palembang and analysis of PPG syllabi and relevant government regulations. Interview data were thematically analyzed, while documents were examined through content analysis to evaluate professional preparedness and identify systemic competency gaps. The findings reveal that, while the programme successfully developed pedagogical, technological, administrative, and professional competencies, these forms of preparedness were largely universal and insufficient for managing multidisciplinary content and diverse classroom needs at the elementary level, positioning formally certified teachers as contextually underprepared. The study found that professional preparedness cannot be ensured through certification alone without alignment between training design and placement context. This research contributes to teacher education by providing evidence to inform policy reform towards level-based teacher preparation and structured support after certification.